Human hepatoma Huh-7 cell culture models deficient in apolipoprotein B secretion - Swati Valmiki; Sara Rosario; Ashley Mooring; Chandana Prakashmurthy; Florencia Schlamp; Binu Prakash; Atrayee Chattopadhyay; Abulaish Ansari; José O. Alemán; Nathalie Pamir; M. Mahmood Hussain (Journal of Lipid Research)
ApoB is an essential structural protein for the assembly and secretion of triglyceride-rich lipoproteins and therefore remains a potential target to lower plasma cholesterol levels in hypercholesterolemia patients. To understand the global consequences of APOB gene deficiency, we employed CRISPR-Cas9 system to generate apoB-deficient human hepatoma Huh-7 cells (Ako cells). ApoB was not detectable in the cells and media of the Ako cells. ApoB deficiency had no effect on microsomal triglyceride transfer protein expression and activity. These cells supported apoB48 secretion when transfected with plasmids for the expression of apoB48 suggesting that these cells retain all the lipoprotein assembly and secretion machinery except for apoB expression. APOB gene deficiency had no significant effect on cellular lipid levels, cell growth, and ER stress markers. Proteome analysis of secreted proteins revealed that the most upregulated protein was the vitamin D binding protein, while the most downregulated protein was apoB in Ako cells compared to control cells. This analysis also identified coagulation as an upregulated pathway. Total RNA transcriptome analysis identified DNA replication and complement and coagulation pathways as the most upregulated pathways in Ako cells. Further detailed studies are needed to establish how apoB regulates these pathways. These Ako cells may be useful in studying structure-function analysis of apoB peptides and to address the cellular consequences of disruptions in lipoprotein assembly and secretion.